Association of Acute Trapeziometacarpal Joint Dislocation and Trapezium Fracture in a 14-Year-Old Boy: A Case Report. (January 2023) - Minini, Andrea; Fagetti, Alessandro; Tamborini, Federico; Di Giovanna, Danilo; Salvi, Andrea G.; Maffeis, Jacopo; Sibona, Federico; Cherubino, Mario
Fracture-dislocation of the trapeziometacarpal (TM) joint in adolescent patients is a rare injury, with only 3 cases reported in literature to our knowledge. Its low incidence, together with the complexity of the anatomy and biomechanics of TM joint, may represent a challenge for surgeons in choosing the best treating option. Here, we report a case of a TM fracture dislocation in a 14-year-old boy treated with percutaneous Kirschner wire pinning. The results we obtained endorsed our choice in patients for whom closed reduction is achievable.